2003
DOI: 10.1111/j.1744-6570.2003.tb00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the Relationship Between the Five‐factor Model of Personality and Holland's Occupational Types

Abstract: The purpose of this study is to examine the nature and magnitude of the relationship between 2 widely accepted models for classifying individual differences–the 5‐factor model of personality and Holland's RI‐ASEC occupational types. Based on extensive meta‐analyses, our results illustrate that there are meaningful relations between some FFM personality dimensions and some RIASEC types. The strongest relationships were obtained between the RIASEC types of enterprising and artistic with the FFM personality dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

60
430
6
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(511 citation statements)
references
References 64 publications
60
430
6
15
Order By: Relevance
“…Another study reports convergence validity between ATPH and the Photos of Professions Test (BBT-Br), equivalent to BBT -Berufsbilder test, masculine and feminine versions (Mansão, Noronha, & Ottati, 2011). Noronha, Mansão and Nunes (2012), in turn, showed that the Holland types are related to the personality traits of the Big Five model, corroborating results from other international studies (Barrick, Mount, & Gupta, 2003;Holland et al, 1994;Larson, Rottinghaus, & Borgen, 2002;Staggs, Larson, & Borgen, 2007).…”
supporting
confidence: 77%
“…Another study reports convergence validity between ATPH and the Photos of Professions Test (BBT-Br), equivalent to BBT -Berufsbilder test, masculine and feminine versions (Mansão, Noronha, & Ottati, 2011). Noronha, Mansão and Nunes (2012), in turn, showed that the Holland types are related to the personality traits of the Big Five model, corroborating results from other international studies (Barrick, Mount, & Gupta, 2003;Holland et al, 1994;Larson, Rottinghaus, & Borgen, 2002;Staggs, Larson, & Borgen, 2007).…”
supporting
confidence: 77%
“…In the work domain in particular, there is now evidence showing that people are interested in and tend to gravitate toward occupational environments that-at least to a certain extent-fit their personality traits (Barrick, Mount, & Gupta, 2003;Betz, Borgen, & Harmon, 2006;De Fruyt & Mervielde, 1999;Gottfredson, Jones, & Holland, 1993;Woods & Hampson, 2010). But what happens with individuals once they are in such environments?…”
mentioning
confidence: 99%
“…These I-P linkages from the metaanalyses included artistic interests and openness, investigative interests and openness, social interests and extraversion, enterprising interests and extraversion, and conventional interests with conscientiousness (excluding women who completed the SII) (Barrick et a!., 2003;Larson et al, 2002). Like Ackerman and Heggestad, these two groups of scholars also did not find realistic interests to be linked to the Big Five.…”
Section: Trait Complexesmentioning
confidence: 94%
“…Scholars have ascertained that some personality traits overlap with some of Holland's six interests (Barrick, Mount, & Gupta, 2003;Larson, Rottinghaus, & Borgen, 2002) and that specific facets of personality predict specific interests (Staggs, Larson, & Borgen, 2003;Sullivan & Hansen, 2004). Self-efficacy across Holland's hexagon and across specific academic domains has been moderately predictive of parallel interests (Rottinghaus, Larson, et a!., 2003).…”
Section: Interestsmentioning
confidence: 99%
See 1 more Smart Citation